Śivalīlāmrtamahākāvyam / Śrīmadagnicítpaṇṣitanityānandaviracitam ; Bhagavān Paṇḍāśarmmaṇā sampāditam - Nityānanda, 17th/18th cent (Utkaliya-prācya-granthamālā. Saṃskrtam, 1978)
Long poem in praise of Śiva, Hindu deity; includes songs.